Transthoracic Echocardiogram Guided Hemodynamic Management to Maintain Cerebral Perfusion in an Extracranial–Intracranial Bypass Case: Case Report - Allen, Beddome C.; Oravec, Chesney S.; Wolfe, Stacey Q.; Vallabhajosyula, Saraschandra; Kapoor, Sahil; Bethina, Sai Varun; Sarwal, Aarti (Journal of Neurological Surgery Reports, 2025)
A 70-year-old man with transient ischemic attacks (TIAs) due to left internal carotid artery (ICA) occlusion underwent external carotid to ICA bypass which occluded postoperatively. He developed aphasia which resolved with induced hypertension optimized by using serial transthoracic echocardiography in the setting of left ventricle outflow tract obstruction.
Keywords: echocardiography; carotid stenosis; hypertrophic cardiomyopathy; transient ischemic attack; cerebrovascular circulation; cerebral revascularization